Synthesis, characterization and Performance of Asymmetric Polyethersulfone (PES) ultrafiltration membranes with polyethylene glycol of different molecular weights as additives - Idris, Ani (http://www.sciencedirect.com, 2007)
This paper reports the performance of asymmetric polyethersulfone ultrafiltration flat sheet membranes with polyethylene glycol (PEG) of different molecular weight as additives. The membranes were prepared by phase inversion process from casting solution containing polyethersulfone (PES) as polymer, N,N-dimethylformamide (DMF) as solvent and PEG of different molecular weights namely as PEG 200, PEG 400 and PEG 600 as additives. The membranes were characterized in terms of pure water permeation (PWP), molecular weight cut off (MWCO), solute separation, flux and membrane morphology. Mean pore size (Î¼p) and standard deviation (Ïƒp) of the membranes were determined using solute transport data. The results revealed that membranes with PEG of higher molecular weights have higher pure water permeation and larger pores. The MWCO of the membranes increased from 26 to 45 kDa when the molecular weight of PEG is increased from 200 to 600. A significant change also occurred in pure water permeation, solute separation and flux when concentration of additives is increased from 5 to 25 wt% in casting solution. The presence of the different PEG molecular weights affect the surface roughness and morphology of the membrane as can be observed from the atomic force microscope (AFM) and scanning electron microscope (SEM) analysis.